Analisis Pengaduan Masyarakat terhadap Pelayanan Publik Melalui Ombudsman Republik Indonesia di Provinsi Sulawesi Selatan - Misbahuddin Misbahuddin; Andi Rahmat Nizar Hidayat (Universitas 17 Agustus 1945 Semarang, Indonesia, 2026)
Public service is a key indicator in evaluating local government performance; however, various service issues continue to generate increasing public complaints. This study aims to analyze trends in public complaints, identify the most frequently reported institutions, and examine the types of maladministration and the status of complaint resolution through the Ombudsman of the Republic of Indonesia in South Sulawesi Province during 2023–2025. This study offers novelty by providing an integrated analysis of complaint trends, distribution of reported institutions, types of maladministration, and resolution outcomes based on Ombudsman data at the regional level. This research employs a qualitative approach using document analysis, with public complaint reports as the unit of analysis. Data were analyzed through data reduction, data display, and conclusion drawing. The results indicate that local governments are the most frequently reported institutions (55.1%), with dominant maladministration types including procedural deviations and prolonged delays. Several complaints were proven to involve maladministration and were resolved through the Ombudsman’s supervisory mechanism. These findings highlight that public complaints serve as an important instrument in enhancing accountability and transparency in public service delivery. Therefore, local governments need to strengthen service standards, improve the capacity of public officials, and develop more effective complaint management systems.